α/β-Hydrolase domain-6 and saturated long chain monoacylglycerol regulate insulin secretion promoted by both fuel and non-fuel stimuli - Shangang Zhao; Pegah Poursharifi; Yves Mugabo; Emily J. Levens; Kevin Vivot; Camille Attane; Jose Iglesias; Marie-line Peyot; Erik Joly; S.R. Murthy Madiraju; Marc Prentki (Elsevier, 2015)
Objective: α/β-Hydrolase domain-6 (ABHD6) is a newly identified monoacylglycerol (MAG) lipase. We recently reported that it negatively regulates glucose stimulated insulin secretion (GSIS) in the β cells by hydrolyzing lipolysis-derived MAG that acts as a metabolic coupling factor and signaling molecule via exocytotic regulator Munc13-1. Whether ABHD6 and MAG play a role in response to all classes of insulin secretagogues, in particular various fuel and non-fuel stimuli, is unknown. Methods: Insulin secretion in response to various classes of secretagogues, exogenous MAG and pharmacological agents was measured in islets of mice deficient in ABHD6 specifically in the β cell (BKO). Islet perifusion experiments and determinations of glucose and fatty acid metabolism, cytosolic Ca2+ and MAG species levels were carried out. Results: Deletion of ABHD6 potentiated insulin secretion in response to the fuels glutamine plus leucine and α-ketoisocaproate and to the non-fuel stimuli glucagon-like peptide 1, carbamylcholine and elevated KCl. Fatty acids amplified GSIS in control and BKO mice to the same extent. Exogenous 1-MAG amplified insulin secretion in response to fuel and non-fuel stimuli. MAG hydrolysis activity was greatly reduced in BKO islets without changes in total diacylglycerol and triacylglycerol lipase activity. ABHD6 deletion induced insulin secretion independently from KATP channels and did not alter the glucose induced rise in intracellular Ca2+. Perifusion studies showed elevated insulin secretion during second phase of GSIS in BKO islets that was not due to altered cytosolic Ca2+ signaling or because of changes in glucose and fatty acid metabolism. Glucose increased islet saturated long chain 1-MAG species and ABHD6 deletion caused accumulation of these 1-MAG species at both low and elevated glucose. Conclusion: ABHD6 regulates insulin secretion in response to fuel stimuli at large and some non-fuel stimuli by controlling long chain saturated 1-MAG levels that synergize with other signaling pathways for secretion.